Предмет: Алгебра,
автор: vip05kurbanmeteev
Упростить выражение;х в кубе-(х в квадрате -3)×(х+3)
Ответы
Автор ответа:
0
x³-(x²-3)(x+3)=x³-(x³+3x²-3x-9)=x³-x³-3x²+3x+9=-3x²+3x+9
Автор ответа:
0
Ой х в квадрате -3 х
Автор ответа:
0
х³-(х²-3)(х+3)=х³-(х³+3х²-3х-9)=х³-х³-3х²+3х+9=3х-3х²+9
Похожие вопросы
Предмет: Русский язык,
автор: udrozdova667
Предмет: Қазақ тiлi,
автор: adamgero562
Предмет: Алгебра,
автор: lyudmilaagisheva78
Предмет: Информатика,
автор: Romantika23
Предмет: Литература,
автор: Лина408